1989
DOI: 10.3109/00365528909092235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bile Salts on Carbonic Anhydrase from Rat and Human Gastric Mucosa

Abstract: Gastric carbonic anhydrase (CA) is believed to play an important role related to cytoprotection, and duodenogastric reflux of bile salts (BS) is suspected of having a causal role in many pathologic conditions. Thus, we decided to investigate the effect of free and conjugated BS on human and rat gastric CA activity. Cholate exerted the most potent inhibitory activity on both human (I50 = 2.24 mM) and rat (I50 = 1.68 mM) gastric CA, followed by glycochenodeoxycholate and taurocholate (I50 = 6.90 mM and 13.67 mM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Firstly, placental expression of CA2 and SLC4A4 , responsible for bicarbonate production and uptake, respectively, were continuously decreased from G60 to L0. Secondly, carbonic anhydrase (CA), including bovine CA and human CA1 and CA2, were potently inhibited by bile salts [34] and showed BA species dependent effect [65,66,67]. In consideration of that CO 2 diffuses across placenta predominantly in the molecular form rather than as bicarbonate ion [33] and the bicarbonate in mother was higher than in fetal unit in normal pregnancy [68], the decreased bicarbonate in placenta may limit BA exchange between fetus and mother in the TPMb.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, placental expression of CA2 and SLC4A4 , responsible for bicarbonate production and uptake, respectively, were continuously decreased from G60 to L0. Secondly, carbonic anhydrase (CA), including bovine CA and human CA1 and CA2, were potently inhibited by bile salts [34] and showed BA species dependent effect [65,66,67]. In consideration of that CO 2 diffuses across placenta predominantly in the molecular form rather than as bicarbonate ion [33] and the bicarbonate in mother was higher than in fetal unit in normal pregnancy [68], the decreased bicarbonate in placenta may limit BA exchange between fetus and mother in the TPMb.…”
Section: Discussionmentioning
confidence: 99%
“…These changes may represent an adaptive response to mucosal injury by gastric reflux.s> Interestingly, total gastric CA activity has been shown to be reduced by bile salts and gastritis and is associated with a decrease in CA I expression. 18, 66 Parkkila et al 67 have also demonstrated a reduction in salivary CA VI levels in patients with esophagitis and gastric and duodenal ulcers.…”
Section: Xi* XIImentioning
confidence: 95%
“…Several isoforms of human CAs (HCAs) along the gastrointestinal tract, including HCA II, are inhibited by the bile acids (BAs; Milov et al, 1992), the primary products of cholesterol catabolism (Staels & Fonseca, 2009). BAs have been shown to damage the gastric mucosa in animals, and duodenogastric reflux is regarded as one pathogenic factor in gastritis, gastric ulcer and alkaline reflux gastritis in the postgastrectomy stomach in humans (Salomoni et al, 1989). The mucosal damaging activity of cholic acid, taurocholic acid and glycochenodeoxycholic acid has been directly associated with gastric mucosal CA inhibition in rats and humans (Kivilaakso, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophilicity of the BAs can be further enhanced before secretion into the bile canalicular lumen of the gall bladder for storage via conjugation with taurine or glycine (Staels & Fonseca, 2009). The strongest binding affinity among the BAs for HCA II include cholic and deoxycholic acid, with I 50 values of $0.1 and 0.4 mM, respectively, as measured using stopped-flow spectrophotometry studies (Salomoni et al, 1989).…”
Section: Introductionmentioning
confidence: 99%